Influence of age and industry experience on learning experiences and outcomes in virtual reality mines rescue training - Pedram, Shiva; Palmisano, Stephen; Miellet, Sebastien; Farrelly, Matthew; Perez, Pascal (Frontiers in Virtual Reality, 2022)
This study examined the effects of age and industry expertise on trainees’ state of mind before, learning experiences during, and outcomes following virtual reality (VR) mines rescue training. The trainees were 284 mine rescue brigadesmen attending group VR training sessions run by Coal Services NSW. They were aged between 24 and 64 years and had up to 40 years of mines rescue experience. Questionnaire data and learning outcome measures showed that these miners were able to effectively engage with, and learn from, this VR training regardless of their age or mining experience. While the older trainees initially reported higher levels of stress and had less gaming experience, their experiences during VR training were very similar (although reports that the VR technology sometimes did not meet the task requirements did increase with age). Crucially, the perceived learning outcomes of this VR training were unaffected by age or field experience.